JEAN PIAGET E O ENSINO DA GEOGRAFIA ESCOLAR: UM OLHAR SOBRE O MAPA (Revista Contexto & Educação, 2020)
This article is part of a doctoral research developed in the Postgraduate Program in Geography of the Federal University of Santa Maria (UFSM) and is designed as an approximation of the teaching of Geography with the Genetic Epistemology of Jean Piaget. For this, we worked with a group of children from a public school in Rio Grande do Sul, located in the municipality of Canoas, metropolitan region of Porto Alegre. The group is formed by students of the 8th year of elementary school in which it was sought to work the reversibility and decentration of thought from the use of the map as a tool to understand the potentialities of thinking of these subjects.